Fractured Landscape, Divided Society, Split Selves—the Blitzed London as ‘Third landscape’ in Rose Macaulay’s The World My Wilderness (1950) - Clémence Laburthe-Tolra (Études Britanniques Contemporaines, 2023)
From her autobiographical short story ‘Miss Anstruther’s Letters’ (1942) to her postwar novel The World My Wilderness (1950), Rose Macaulay explores the devastating effects of war on London, its cityscape, society and inhabitants. Confronted to the bombing of her flat during the Blitz as recalled in ‘Miss Anstruther’s Letters,’ Macaulay expands on this traumatising event in The World My Wilderness and depicts outcasts rambling in the ruins amidst fault lines, be they architectural, geological or psychological. This paper examines The World My Wilderness via the prism of the ‘third landscape’ as defined by Gilles Clément in recent landscape theory (2020). Drawing on Clément’s concept, I contend that the ‘broken city’ (Macaulay, 45) provides a space of in-betweeness for outcasts and biodiversity, as Rose Macaulay invests the fractures scarring landscape, society and individuals at a time when the preservation of ruins was much debated.